2019
DOI: 10.3390/polym11122000
|View full text |Cite
|
Sign up to set email alerts
|

Durable Antimicrobial Behaviour from Silver-Graphene Coated Medical Textile Composites

Abstract: Silver nanoparticle (AgNP) and AgNP/reduced graphene oxide (rGO) nanocomposite impregnated medical grade polyviscose textile pads were formed using a facile, surface-mediated wet chemical solution-dipping process, without further annealing. Surfaces were sequentially treated in situ with a sodium borohydride (NaBH4) reducing agent, prior to formation, deposition, and fixation of Ag nanostructures and/or rGO nanosheets throughout porous non-woven (i.e., randomly interwoven) fibrous scaffolds. There was no need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 142 publications
(165 reference statements)
0
29
0
1
Order By: Relevance
“…Ag ions can interact with the cell membranes, nucleic acids and proteins of the bacteria via ligand exchange reactions to exert their activity [26]. Additionally, the direct interaction of Ag nanoparticles with the surface of bacterial cells also plays an important role in their antibacterial activity [45].…”
Section: Antibacterial Activities Of Pom/ag Nanocompositesmentioning
confidence: 99%
“…Ag ions can interact with the cell membranes, nucleic acids and proteins of the bacteria via ligand exchange reactions to exert their activity [26]. Additionally, the direct interaction of Ag nanoparticles with the surface of bacterial cells also plays an important role in their antibacterial activity [45].…”
Section: Antibacterial Activities Of Pom/ag Nanocompositesmentioning
confidence: 99%
“…A medical grade polyviscose textile pads were formed by impregnation of Ag nanoparticle decorated rGO nanocomposite through wet chemical solution dipping process. It is also reported that rGO increasing the stability of Ag nanoparticles onto textile fabric substrates which enhanced rinse-reuse capabilities and antimicrobial properties [40] . Many companies have claimed that graphene can be used to make gloves, masks and gowns for medical staff.…”
Section: Graphene Textile For Protection Against Virusmentioning
confidence: 99%
“…By leaching test, it has been reported that even after accelerated washing cycles the novel composites exhibited high silver loading and high bactericidal activity over six hours of treatment. It has been reported that reduced graphene oxide -silver nanoparticles showed nearly 100% antibacterial activity against Ecoli [41].…”
Section: Graphene Oxide -Silver Nanoparticles (Go-ag)mentioning
confidence: 99%